The addition of aluminum to brittle martensitic steels in order to increase ductility by forming a grain boundary ferritic microfilm. (May 2022) - Pinson, M.; Das, S.M.; Springer, H.; Depover, T.; Verbeken, K.
Abstract: The addition of 2 wt% of aluminum to a Fe-0.4 wt% C martensitic steel led to the formation of a ferritic microfilm along the prior austenitic grain boundaries after austenitization and quenching. Both materials with and without Al exhibited a similar bulk hardness of 580 HV3 owing to their predominantly martensitic microstructure. Bending tests and the analysis of the corresponding fracture surfaces revealed a ductile fracture of the ferritic microfilm opposed to an intergranular fracture behavior of the samples without Al, which translated into a significantly increase in the bulk ductility of the Al-alloyed steel by more than 100%. These results open up new grain boundary engineering opportunities to increase the ductility of hard and otherwise brittle steels. Graphical abstract: Image, graphical abstract